Pelatihan Penilaian Mandiri Masyarakat dan Institusi Melalui Aplikasi Android dalam Pengurangan Risiko Bencana Covid-19 - Muchsin Riviwanto; Burhan Muslim; Alsri Windra Doni; Defriani Dwiyanti (CV. CENDIKIA JENIUS INDONESIA, 2024)
The health center which is the first referral must provide complete health services and quick action for disaster victims. The purpose of the activity is for participants to be able to understand the reduction of the risk of covid 19 disasters based on android. The method of activity is by providing training using the reduction of the risk of covid 19 disasters based on android. The results of community service show that most of the training participants are female (90%). Based on age group, the majority are in the age group over 35 years. As many as 60% are at the PT education level and half are health workers and half are health cadres. The evaluation showed that before being given training on disaster vulnerability management, the level of understanding of participants was high at 40% and the level of ability was high at 20%. However, after being given participatory mapping material, the level of knowledge of participants was high at 90% and the level of ability of participants was high at 95%. Conclusion: by preparing documents, evacuation planning, increasing public awareness, and preparing the health team well, we can improve the response and mitigation of the impact of disasters effectively